Transformasi Bentuk Ka’bah Sebagai Pendekatan Perancangan Bentuk Masjid Agung Darussalam Kota Palu - Halima, Halima; Arifin, Rosmiaty; Arafat, Yasir; Tamimi, Nadil; Sudiyatama, Andi Farid; Irfandi, Irfandi (JURNAL RUANG / ISSN : 2085-6962, 2025)
The Great Mosque of Darussalam in Palu suffered severe damage due to the 2018 earthquake, necessitating a redesign that not only meets functional needs but also reflects Islamic symbolism. This study aims to redesign the mosque by adopting a transformation approach based on the form of the Kaaba, the central spiritual symbol in Islamic architecture. The research employs a qualitative descriptive method through literature review, contextual observation, and morphological analysis. The transformation is carried out using subtractive and additive techniques applied to the basic cubic form of the Kaaba, resulting in a mosque design that is monumental, contextual, and rich in symbolic meaning. The final design also incorporates principles of tropical architecture and local elements of Kaili culture, creating a mosque that is not only aesthetically and spiritually significant but also relevant to the post-disaster social and geographical context of Palu City